UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENCEGAH PRILAKU MENYIMPANG SISWA DI SEKOLAH - Ifnaldi (El-Rusyd, 2022)
Guidance and councelling service is supposed to achievemend education and realization of councelling purpose. Preventive function is guidance and councelling fuction that has relation with councellor efforts to anticipate every problem that may happend and try to solve it so that faced by the learners. Infact, deviatiom action can be happened anywhere, like in the traditional society in the village, in the city or modern society.